#TITLE_ALTERNATIVE# - (NIM 10107080); Pembimbing : Dr. Sri Redjeki Pudjaprasetya, IRYANTO
Pressure difference between inside the reservoir with pressure at the base production wells causes crude oil to flow out. When the flow stops, most of the oil will remain trapped in reservoir rocks. This trapped oil can not flow out through the production wells by themselves. Therefore, the additional thrust needed to force the oil out. One method that is common used in secondary recovery is to inject water into the reservoir through injection wells. Mathematical model that describes the displacement process is the Buckley-Leverett equation. This final project discusses the Buckley-Leverett equation. Analytical solution of the Buckley-Leverett equation that satisfies the entropy condition can be constructed through convex hull principle. The solution consists of shock wave and rarefaction wave. Shock wave velocity determine the speed oil discharge in this secondary recovery. Numerical solution is calculated using the Godunov method. This final project begin with a description of the Burgers equation which is the simplest form of the Buckley-Leverett equation.